Computer Confluence: Exploring Tomorrow's Technology - Beekman, George (Singapore, 2000)
When powerful forces come together, change is inevitable. As the 20th century comes to a close, we're standing at the confluence of three powerful technological forces: computers, telecommunications, and electronic entertainment
Keywords: Computers; Information Technology